An Improved Method for Smoothing and Interpolating Hourly Sea Level Data - Karunaratne, D. A. (The International Hydrographic Review, 2015)
A method for smoothing and interpolating observed hourly digital tidal elevations is presented. The method which is based on fitting a small number of harmonic tidal components to the data series has proved to be superior to standard smoothing procedures and can be applied to data from different tidal regimes. The method is relatively simple, economical, and can be executed on standard digital computers with limited storage capacity.